2021
DOI: 10.3390/plants11010091
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Mitigates Negative Impacts of Drought and UV-B Radiation in Plants

Abstract: Due to climate change, plants are being more adversely affected by heatwaves, floods, droughts, and increased temperatures and UV radiation. This review focuses on enhanced UV-B radiation and drought, and mitigation of their adverse effects through silicon addition. Studies on UV-B stress and addition of silicon or silicon nanoparticles have been reported for crop plants including rice, wheat, and soybean. These have shown that addition of silicon to plants under UV-B radiation stress increases the contents of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…The elevated levels of the flavonoid contents indicated that Si may be important in the antioxidant defenses that occurred in response to the droughts, especially in the more drought-sensitive grass species. The exogenous application of silicon could alleviate the oxidative stress of the plants through the modification of the biosynthesis of reactive species and the transcriptional regulation of multiple defense pathways, such as antioxidant enzymes, antioxidant active substances, and also flavonoid compounds [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The elevated levels of the flavonoid contents indicated that Si may be important in the antioxidant defenses that occurred in response to the droughts, especially in the more drought-sensitive grass species. The exogenous application of silicon could alleviate the oxidative stress of the plants through the modification of the biosynthesis of reactive species and the transcriptional regulation of multiple defense pathways, such as antioxidant enzymes, antioxidant active substances, and also flavonoid compounds [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Si application on several plant species has been proven for several decades, and research has shown numerous advantageous effects of Si on different plant attributes including vegetative growth, development, production, and reduction of biotic and abiotic stress [ 3 , 4 , 5 , 6 ]. Other Si-driven benefits include increase in photosynthetic rate, lower transpiration rate, and resistance to UV-B radiation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of these flavonoids and derivatives is important during an environmental stress response. Flavonoids have been reported to play a role in the maintenance of ROS homeostasis ( Chen et al, 2019 ; Mavrič Čermelj et al, 2021 ) also. In the present study, higher ROS levels (H 2 O 2 and O 2 – activity) were also detected in rice under dry cultivation compared with flooding treatment ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Drought and its relationship with silicon have been well studied. For example, in some plants such as sugarcane ( Saccharum officinarum L.), wheat ( Triticum aestivum L.) under drought stress, silicon increases ascorbate peroxidase activity, total soluble sugars content, relative water content ( Mavrič Čermelj et al, 2021 ). In some studies, on rice ( Oryza sativa L.) was found in Si induced different responses regarding to proline accumulation which could be beneficial for drought exposed plants ( Mauad et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%